Social recognition in male rats: age differences and modulation by MIF-I and Alaptide - Hlinák, Z; Krejcí, I (Physiological research, 1991)
Social investigatory behaviour was used as a measure of olfactory recognition in two experiments to assess social memory in adult male rats. In Experiment 1, time spent in social investigation of juvenile males by 3-month-old adults was significantly higher than time spent by 7- and 11-month-old animals. Furthermore, a reexposure to the same juvenile male 30 min after the initial exposure elicited significantly less social investigation in adult males aged 7 and 11 months but not in those aged 3 months. If the reexposure occurs 2 h later, the same juvenile is thoroughly investigated by adult males irrespective of the age. The age-related differences in social recognition are discussed in terms of the internal readiness of adult males. While the social recognition was confirmed in older adult males, it is suggested that an ability to recognize the same juvenile may be masked in young animals by a high sexual arousal. Behavioural phenomenon of the social recognition was used in Experiment 2. An administration of hypothalamic MIF-I or its synthetic derivative Alaptide to adult males 7 or 11 months old immediately after their 1st exposure to a juvenile male resulted in decreasing the time spent in social investigation of the same juvenile during a reexposure performed 120 min later. Both drugs were ineffective if adult males were reexposed to a novel juvenile. The results suggest that both MIF-I and Alaptide improved an animal's capacity to store information received through olfactory cues.
Keywords: Aging; Smell; Male; Rats; neuropeptidy; inbrední kmeny potkanů; stárnutí; Neuropeptides; sociální chování; hypothalamus; Animals; čich; zvířata; Social Behavior; mužské pohlaví; Rats, Inbred Strains; MSH Release-Inhibiting Hormone; Peptides, Cyclic; krysa rodu Rattus; hormon inhibující uvolňování MSH; cyklické peptidy; Hypothalamus